Patching the Pathway and Widening the Pipeline: Models for Developing a Diverse Early Childhood Workforce in Chicago. Issue 3 (21st January 2019) - Zinsser, Katherine M.; Main, Catherine; Torres, Luz; Connor, Kate
Abstract: With the growing appreciation of the importance of early learning experiences for children's healthy development, attention to the cultivation and maintenance of a qualified workforce has steadily increased. Such a workforce must have not just the knowledge and skills related to child development and early learning, but also be linguistically and culturally prepared to meet the needs of an increasingly diverse child and family population. To ensure a highly qualified workforce, programs and policymakers must attend to both the "pipeline" through which new early childhood educators (ECEs) enter the workforce and the "pathways" by which ECEs work toward and obtain the necessary education and credentials for different roles within the field. In line with the aims of this special issue, this paper leverages the first‐person account style to describe barriers to and creative solutions for the development of practitioners in low‐resourced communities in Chicago, with the goal of informing practice and policy. We describe three prior and ongoing partnership programs between community‐based organizations and institutions of higher education, each tailored to support a unique population in the ECE pipeline on the pathway for increased educational attainment and credentialing. Each program is grounded in a specific community of Chicago, a diverse city with a sizable population of children raised in non‐English speaking homes. Each program addresses specific needs of the communities they serve, especially around the recruitment, retention, and promotion of bilingual ECEs. Program administrators and community members describe each programs' goals, development, and key components unique to their target population as well as key takeaways. We conclude with an overview of critical components that we identified across these programs in order to create pathways for change within the workforce and the communities they serve. Highlights: There is a national shortage of high‐quality early childhood educators. The workforce pipeline must be expanded to increase cultural and linguistic preparedness. This paper highlights three Chicago‐based partnerships to increase workforce skill and diversity. Each "grow‐your‐own" program is designed to meet the specific needs of the communities they serve. These community‐responsive examples can inform national conversation about workforce development.